Gate length effect on trapping properties in AlGaN/GaN high-electron-mobility transistors. (11th March 2019) - Ferrandis, Philippe; El-Khatib, Mariam; Jaud, Marie-Anne; Morvan, Erwan; Charles, Matthew; Guillot, Gérard; Bremond, Georges
Abstract: A comparative study was performed to assess the gate length effect on trapping properties in AlGaN/GaN metal-oxide-semiconductor channel high-electron-mobility transistors. Deep level transient spectroscopy and electrical simulations were used to investigate the deep levels response in two devices with the same gate surface area but with gate lengths of 15 and 1 μ m. Results reveal that the repartition of equipotential lines depends on the gate length and impacts trapping phenomena. We demonstrated that the concentration of the defects localized beneath the gate electrode and associated with etching induced damage is reduced with a short gate length. Furthermore, for a negative gate voltage, the depletion region is less extended toward the buffer layers with a gate length of 1 μ m, meaning that the trapping effects are reduced. Finally, this work indicates that it is better to design transistors with a short gate length to moderate the effect of trapping phenomena.